Saudi Arabia Socio-Cultural Reform in Saudi Vision 2030 - Salma Salsabila; Mohammad Izdiyan Muttaqin (Universitas Muhammadiyah Gorontalo, 2022)
Socio-cultural reforms carried out by Saudi Arabia are based on a rational consideration to maintain the country’s existence in the midst of increasingly strong currents of globalization and modernism. The image of Saudi Arabia in the international arena, which is famous for its rigid and conservative teachings of Wahhabism, is gradually being changed to suit the global social order. At the same time, this change is still striving to preserve cultural values that have become the identity of Saudi Arabia, as the beginning of world Muslim civilization. This socio-cultural reform trend strengthened along with the change in the peak of Saudi Arabia's government, which was marked by the ascension of Muhammad Bin Salman as the Crown Prince, who has control in determining the direction of strategic policies domestically and internationally. Through Saudi Vision 2030, this socio-cultural reform can be carried out in a measurable and systematic way to achieve the goal of economic diversification and ensure the existence and dominance of the country in the future. The author will use a qualitative research system with analytical descriptive methods that utilize various sources such as scientific articles, journals, books, media, and other sources that have been processed and studied. This study will use the theory of national interest and rational choice to identify the decision- making process in carrying out socio-cultural reforms through Saudi Vision 2030. The results show that Saudi Vision 2030 plays a significant role as a manifestation of Saudi Arabia's socio-cultural reform-based policies.